A Sound-Based Monitoring and Evaluation System for Small-Scale Dairy Operations - Songül Şentürklü; Ertuğrul Bilgücü; A. Cumhur Kınacı; Sefa Aksu; Ünal Kızıl (Journal of Advanced Research in Natural and Applied Sciences)
Continuous monitoring of livestock operations is vitally important for a sustainable production system. Monitoring systems based on cameras are not sufficient in livestock barns since they require visual inspection and ignore vocal conditions within the barn. These systems are also quite expensive for most small family operations. A prototype device that costed $ 470 was developed to remotely monitor the barn based on sound sensors (microphones) data. This device also warns the operator by sending an SMS at sound intensities exceeding the predetermined durations and threshold values. It also makes it possible to listen to the barn by phone if needed. The device and associated web database was tested in this study. The main challenge was the determination of threshold values at which sensors are to generate warning SMS messages. As a method, Z-score of 2.33 which corresponds to area left of the 99% of the normally distributed data curve was determined representing the highest values with a possibility of 1% observation for each sensor. An average value of 97 dB was determined to be a threshold suggestion for future studies. A customizable web-based MySQL database was created to monitor and evaluate the long term data collected via the system.